Systematic Literature Review terhadap Keterampilan Dasar Mengajar - Harjun; ST. Asiyah Adzaniah Herul; Putu Dhyana Murti; M. Ridwan Teguh; Muhammad Nazriel Ali Imran Rasyid; Miftachul Jannah Arif; Ines Pratiwi; Alisa Nurul Aska; Fitra Zaulah; Murtina Dewi; Wa Ode Eliza Firdayanti Moris; Dimas Rantangi (Jurnal Ilmiah Literasi Indonesia, 2025)
Basic teaching skills are essential competencies that every teacher must master to create an effective, meaningful, and student-centered learning process. However, several studies reveal that many teachers in Indonesia still face challenges in applying these skills optimally, particularly in explaining learning materials, managing classrooms, and motivating students to engage actively in the learning process. This study aims to analyze the implementation and mastery of basic teaching skills across different educational levels using a Systematic Literature Review (SLR) approach. The review was conducted through three main stages planning, implementation, and reporting by examining 20 scientific articles published between 2017 and 2025, obtained from reputable databases such as Google Scholar, GARUDA, and DOAJ. The findings show that most teachers have developed sufficient skills in opening and closing lessons, providing reinforcement, and managing classrooms effectively. However, weaknesses remain in the areas of explaining content clearly and facilitating small-group discussions. Factors such as limited professional training, inadequate facilities, and excessive administrative workloads hinder the development of basic teaching competencies. Despite these challenges, strategies such as microteaching, lesson study, and continuous professional development have proven effective in enhancing teachers’ pedagogical skills. This study recommends integrating digital learning technologies, promoting reflective academic supervision, and strengthening the role of teacher education institutions in building professional teaching competence. The results are expected to provide practical insights for improving teacher professionalism and advancing adaptive learning practices aligned with 21st-century educational demands.